D–A–D-type bipolar host materials with room temperature phosphorescence for high-efficiency green phosphorescent organic light-emitting diodes. Issue 5 (6th January 2020) - Wang, Fei; Sun, Jing; Liu, Mingli; Shi, Huifang; Ma, Huili; Ye, Wenpeng; Wang, Hua; Zhang, Hongmei; An, Zhongfu; Huang, Wei
Abstract : Bipolar host materials with D–A architectures play an important role in the high efficient PhOLEDs owing to the excellent carrier transport capability, which could be optimized by tight and regular molecular arrangement. Abstract : Bipolar host materials with donor (D)–acceptor (A) structures play an important role in high-efficiency phosphorescent organic light emitting diodes (PhOLEDs) owing to the excellent carrier transport capability, which can be optimized by a tight and regular packing mode in the molecular aggregation. Notably, this arrangement is also beneficial for enhancing intersystem crossing channels and reducing the non-radiative transition for realizing room temperature phosphorescence (RTP). On this basis, RTP materials with a rigid packing mode as the host could be utilized to prepare high-quality devices. Herein, we design and synthesize two bipolar D–A–D molecules constructed by utilizing pyrimidine as an acceptor unit, and dibenzothiophene and dibenzofuran as the donor units, named MDBT and MDBF, respectively, exhibiting considerable RTP performance. In particular, MDBT possesses a longer phosphorescence lifetime (25.1 ms) than MDBF (4.9 ms). From the single crystal analysis, MDBT has a relatively planar configuration through the intramolecular S–N bond. Meanwhile, it is arranged in a compact mode due to the presence of S–S, C–H⋯S and S–π bonds, which suppress the molecular vibration and rotation. Moreover, the rigid structure of MDBT is also certified to be conducive to the formation of a nanoscale high-quality film and charge transport. Significantly, the MDBT -based device doped with 8 wt% Ir(ppy)2 (acac) exhibits a very low turn-on voltage (2.7 V) and a high electroluminescence efficiency (85.00 cd A −1, EQE = 23.03%). Even at the practical luminance of 5000 cd m −2, the efficiencies remain high (81.09 cd A −1, EQE = 21.97%), making MDBT a promising candidate as the host material for green PhOLEDs.